Mimicking localized surface plasmons with structural dispersion - Li, Zhuo (2021)
One major obstacle in developing plasmonic devices is dissipative loss. Structural waveguide dispersion offers a route to tackle this problem. Although long range propagation of surface waves using this concept is recently reported, experimental realizations of localized surface plasmon resonances with suppressed dissipative loss still remain elusive. In this paper, effective localized surface plasmons in a bounded waveguide filled with only positive dielectrics are modeled theoretically and demonstrated experimentally. Theoretical analysis based on cylindrical wave expansion shows that the effective surface modes are induced by structural dispersion of transverse electric modes. Owing to dramatically suppressed metallic loss, the designed structure can support multipolar sharp plasmonic resonances, which are difficult to attain with natural plasmons at optical frequencies. To probe the characteristics of these resonances in the experiment, a deep-subwavelength open resonator is fabricated and the transmission spectrum at the boundary of the structure is measured. The results reveal that structured-dispersion-induced localized surface plasmons are quite sensitive to the background refractive index but relatively robust to the size and shape of the resonator. These findings open up a new avenue for designer localized surface waves at low frequencies and may find applications in miniaturization of microwave resonators, filters, and terahertz biosensors.